The Effect of Ambidextrous Leadership and Social Capital on Competitive Advantage With Entrepreneurship Orientation as A Mediation Variable: A Study on MSMEs in South Tangerang - Wahyudi, Wahyudi; Eryanto, Henry; Santoso, Budi (Universitas Nusantara PGRI Kediri, 2023)
Research aim : This study aims to identify and analyze the factors that influence competitive advantage and provide suggestions for improvement to MSMEs in South Tangerang. Design/Method/Approach : In this study, the variables chosen as predictors of competitive advantage were ambidextrous leadership, social capital, and entrepreneurial orientation. This research is a type of quantitative research. Researchers will use 285 samples, namely the owner or main manager of SME company managers, with a minimum number of 3 employees, have good capital and operatimg in the city of South Tangerang with the business field of community consumption products that have been registered on the Small and Medium Enterprises Cooperatives of South Tangerang Office. The analytical method of this study uses descriptive analysis, validity test, reliability test, while data analysis test of Structural Equation Modeling (SEM) and Multi Analysis Group (MGA). Research Finding : The results of the study prove that (1) ambidextrous leadership has a direct positive effect on entrepreneurial orientation; (2) social capital has a direct positive effect on entrepreneurial orientation; (3) ambidextrous leadership has no direct positive effect on competitive advantage; (4) social capital has a direct positive effect on competitive advantage; (5) entrepreneurial orientation has a direct positive effect on the competitive advantage of employees; while (6) entrepreneurial orientation acts as a partial mediation variable between ambidextrous leadership and employee competitive advantage; and (7) entrepreneurial orientation acts as a partial mediation variable between social capital and competitive advantage. Theoretical contribution/Originality : - Practitionel/Policy implication : - Research limitation : -